GOVERNANCE EFFECTIVENESS: FINDING THE OBJECTIVE CONCEPTUALIZATION AND EVALUATION - Kamolikova, V.R.; Shulika, Y.E. (RUDN Journal of Political Science, 2018)
The paper critically analyzes certain approaches in political science literature to understanding the efficiency. Moreover, there are certain problems of its operationalization and quantitative measurement. The authors question accuracy and “objectivity” of the existing concepts and methodologies used by empirical databases on an assessment of state efficiency. The research sets the purpose to reach the “more objective” efficiency which would respond the principles of valuable neutrality (absence of normativism), relevance and generality (suitable for any case regardless of a political regime, form of government, etc.), creating the conceptual frame and operationalization. Authors take an attempt to represent an approach to the “objective” efficiency as the ability of the state to transform its resources into socially significant results with minimal costs. This is supposed to be possible with Data Envelopment Analysis, which provides the production function of effectiveness by using input and output empirical data.